Intelligent Control Frequency Microgrid in Islanded Mode by Central Protection Unit - Hajihosseini, Mojtaba; Abedi, Ali Akbar; Nakhaei, Dariush; Hajihosseini, Mohammad Haidi (Ciência e Natura, 2015)
The appearance of microgrids created challenges such as microgrid protection and due to the presence distributed generation in microgrid network fault currents basically are variable.protection projects based on constant current must be upgraded.one of the major challenges, changes of microgrid frequency in islanded mode.in this paper a new protection system have provided to monitor microgrids and update current errors use extensive communication network. This system has been designed to respond to the dynamic changes in the system like connection/disconnection DG sources and changing microgrid user condition from connected network mode to islanded mode. the protection system Provided takes over control frequency microgrid in islanded mode and prevents microgrid instability. To control frequency central protection unit changes one of the distributed generators to busbar slack. Studies for the provided network sample have been done and show how the proposed protection system can run these models.